New furoisocoumarins and isocoumarins from the mangrove endophytic fungus Aspergillus sp. 085242 - Xiao, Ze’en; Chen, Senhua; Cai, Runlin; Lin, Shao’e; Hong, Kui; She, Zhigang (Beilstein Journal of Organic Chemistry, 2016)
The chemical investigation of the mangrove endophytic fungus Aspergillus sp. 085242 afforded eight isocoumarin derivatives 1–8 and one isoquinoline 9. Asperisocoumarins A and B (1 and 2) were new furoisocoumarins, and asperisocoumarins E and F (5 and 6) were new isocoumarins. Their structures were established by analysis of their spectroscopic data and the absolute configuration of compound 2 was unambiguously determined by X-ray structure analysis and ECD calculation. Moreover, the absolute configurations of compounds 3–5 were assigned by comparison of their ECD spectra with isocoumarins described in the literature. Asperisocoumarins C and D (3 and 4) were fully characterized spectroscopically and isolated from a natural source for the first time. Asperisocoumarins A–D (1–4) related to the class of furo[3,2-h]isocoumarins are rarely occurring in natural sources. Compounds 2, 5, and 6 showed moderate α-glucosidase inhibitory activity with IC50 of 87.8, 52.3, and 95.6 μM, respectively. In addition, compounds 1 and 3 exhibited weak radical scavenging activity with EC50 values of 125 and 138 μM, respectively.
Keywords: α-glucosidase; Aspergillus; DPPH·; furoisocoumarin; isocoumarin